Confidence sets in nonparametric calibration of exponential Lévy models - Jakob Söhl (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Confidence intervals and joint confidence sets are constructed for the nonparametric calibration of exponential Lévy models based on prices of European options. This is done by showing joint asymptotic normality for the estimation of the volatility, the drift, the intensity and the Lévy density at nitely many points in the spectral calibration method. Furthermore, the asymptotic normality result leads to a test on the value of the volatility in exponential Lévy models.
Keywords: G13; C14; 330; European option; jump diffusion; confidence sets; asymptotic normality; nonlinear inverse problem; Optionspreistheorie; Stochastischer Prozess; Nichtparametrisches Verfahren; Schätztheorie; Theorie